Os rostos na obra “Criança Tapeba”, do fotógrafo José Albano: uma leitura da imagem dos povos indígenas do Brasil - Rodrigues, Claúdia Alexandra António (2020)
The present research proposes an analysis of the photographic series Criança Tapeba (1988), by the Ceará photographer José Albano, produced in a moment of reorganization of the indigenous populations of Ceará, who were opposed to the idea, built since the middle of the 19th century, of the absence of indigenous peoples in Ceara. At that time, the Tapeba people were transitioning their posture from of silent ethnicity to one of affirmation and search for recognition of their identity. Being Criança Tapeba a work that aims to strengthen the indigenous identity affirmation of the Tapeba people, the present research reflects on how this affirmation was built and materialized in these images from the order of the work to the images produced, including their production. With a total count of forty-eight photographs that constitute the work, in its most extensive publication, I took as reference and considered for this research the ten photographs present in the book José Albano: 40 anos de fotografia by José Albano. Taking on the vast imagery context about native peoples, produced over the centuries, in which the images are inserted, their analysis was built through the rescue of the different phases of the life of those images. The present work intends to give another contribution to the study of the images of the Brazilian native peoples, as well as to bridge the research gap on photographs produced in Ceará and by Ceará people - especially photographs that concern the indigenous people. From a methodological point of view, this work took into account the relationship between the gesture of the “man of tautology” and the “man of belief” (Didi-Huberman, 1998) and the concepts studium and punctum,, by Roland Barthes (1984). In addition to authors linked to the study of images, this dissertation dialogues with Hans Belting's concepts of endogenous and exogenous images (2005 and 2007), in their relationship with the production of images of the other and in the construction of stereotypes (Peter Burke, 2017). In this work, is also developed a reflection on the face, guided by the contributions of some authors such as Hans Beting (2007; 2019) and Gabriela Reinaldo (2020a; 2020b). At this point is also relevant to discuss the faces of the photographed children - the face as an identity and ethnic indicator - and to understand how those faces are placed before the stereotyped idea of the existence of a unique and homogeneous indigenous phenotype. We also count with the contribution of Annateresa Fabris (2004) in her reflection on the social uses of the portrait. In addition to documentary and bibliographic research, this investigation is also the result of fieldwork with the people involved in the work, such as the Tapeba people, the photographer José Albano, the interlocutors of the entities who placed the order of the photographs and photographers-researchers who are part of the Ceará scene. In view of the heterogeneity of the features present in the portraits of the Tapeba children, although shaped in their production by a look that follows a pre-established model of Indianity, the Criança Tapeba's images are freed and become independent, acting in the deconstruction of the stereotypes that, at first, shaped them. Keywords: Photography. José Albano. Tapeba. Indigenous people. Indianity model. Face